Training on Grant Proposal Preparation for Non-Profit Organizations in Lhokseumawe City - Zusma Widawaty A. Wahab; Elvina Elvina; Nurmila Dewi; Rahmi Raihan; Yetty Tri Putri (Ridwan Institute, 2023)
One of the manifestations of the Tri Dharma of Higher Education is the implementation of the application of science and technology through training charged to the teaching staff of the Lhokseumawe State Polytechnic. This training is a hands-on practice on preparing grant proposals for non-profit organizations in Lhokseumawe City. This training aims to help improve the capacity of program staff in drafting grant proposals. The material provided in this training consists of preparing a workplan, logical frame work, and budget. This training took place successfully, this can be seen from the success achieved, where 95% of participants already understand how to make grant proposals for non-profit organizations and 5% of participants still have to learn it with the guidance of participants who are already proficient.